Wet deposition of mercury in Qingdao, a coastal urban city in China: Concentrations, fluxes, and influencing factors. (February 2018) - Chen, Lufeng; Li, Yanbin; Liu, Chang; Guo, Lina; Wang, Xiulin
Abstract: Mercury (Hg) is a global pollutant of public concern because of its high toxicity and capability for worldwide distribution via long-range atmospheric transportation. Wet atmospheric deposition is an important source of Hg in both terrestrial and aquatic environments. Concentrations of various Hg species in precipitation were monitored from March 2016 to February 2017 in a coastal urban area of Qingdao, and their wet deposition fluxes were estimated. The results showed that the volume-weighted mean (VWM) concentrations of total mercury (THg), reactive mercury (RHg), dissolved THg (DTHg), particulate THg (PTHg), total methylmercury (TMeHg), and dissolved and particulate MeHg (DMeHg and PMeHg) in Qingdao's precipitation were 13.6, 1.5, 5.4, 8.2, 0.38, 0.15, and 0.22 ng L −1, respectively, and their annual deposition fluxes were estimated to be 5703.0 (THg), 666.6 (RHg), 2304.0 (DTHg), 3470.4 (PTHg), 161.6 (TMeHg), 64.0 (DMeHg), and 95.7 (PMeHg) ng m −2 y −1, respectively. A relatively high proportion of MeHg in THg was observed in precipitation (3.0 ± 2.6%) possibly due to higher methylation and contributions from an oceanic source to MeHg in the precipitation. Obvious seasonal variations in Hg concentrations and deposition fluxes were observed in the precipitation in Qingdao. Correlation analyses and multiple regression analyses showed that SO2, pH, and NO3 − were the controlling factors for THg in precipitation, whereas the MeHg concentration was primarily controlled by the SO2, WS, Cl −, and THg concentrations. PM2.5 and Cl − were the major controlling factors for PMeHg/TMeHg, whereas the TMeHg/THg ratio was mainly influenced by Cl − . The THg and MeHg fluxes were primarily controlled by precipitation, whereas Cl − was also an important factor for the MeHg wet deposition flux. The results of a 72-h backward trajectory analysis in the study region with the Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model indicated that Hg deposition in Qingdao mainly originated from four major sources, i.e., the local area, northwestern China, southeastern China and an oceanic source. This oceanic source is an important source of Hg (especially MeHg) in the precipitation in Qingdao. Highlights: Mercury in precipitation and wet deposition flux were determined in Qingdao. Controlling environmental factors for Hg in precipitation were identified. Precipitation amount is the most important factor for Hg wet deposition in Qingdao. The oceanic source is the most important source of MeHg in Qingdao's precipitation.